Penicillium expansum: biology, omics, and management tools for a global postharvest pathogen causing blue mould of pome fruit - Luciano‐Rosario, Dianiris; Keller, Nancy P.; Jurick, Wayne M. (Molecular plant pathology, 2020)
Blue mould, caused primarily by Penicillium expansum, is a major threat to the global pome fruit industry, causing multimillion‐dollar losses annually. The blue mould fungus negatively affects fruit quality, thereby reducing fresh fruit consumption, and significantly contributes to food loss. P. expansum also produces an array of mycotoxins that are detrimental to human health. Management options are limited and the emergence of fungicide‐resistant Penicillium spp. makes disease management difficult, therefore new approaches and tools are needed to combat blue mould in storage. This species profile comprises a comprehensive literature review of this aggressive pathogen associated with pomes (apple, pear, quince), focusing on biology, mechanisms of disease, control, genomics, and the newest developments in disease management. Taxonomy Penicillium expansum Link 1809. Domain Eukaryota, Kingdom Fungi, Phylum Ascomycota, Subphylum Pezizomycotina, Class Eurotiomycetes, Subclass: Eurotiomycetidae, Order Eurotiales; Family Trichocomaceae, Genus Penicillium, Species expansum. Biology A wide host range necrotrophic postharvest pathogen that requires a wound (e.g., stem pull, punctures, bruises, shoulder cracks) or natural openings (e.g., lenticel, stem end, calyx sinus) to gain ingress and infect. Toxins Patulin, citrinin, chaetoglobosins, communesins, roquefortine C, expansolides A and B, ochratoxin A, penitrem A, rubratoxin B, and penicillic acid. Host range Primarily apples, European pear, Asian pear, medlar, and quince. Blue mould has also been reported on stone fruits (cherry, plum, peach), small fruits (grape, strawberry, kiwi), and hazel nut. Disease symptoms Blue mould initially appears as light tan to dark brown circular lesions with a defined margin between the decayed and healthy tissues. The decayed tissue is soft and watery, and blue‐green spore masses appear on the decayed area, starting at the infection site and radiating outward as the decayed area ages. Disease control Preharvest fungicides with postharvest activity and postharvest fungicides are primarily used to control decay. Orchard and packinghouse sanitation methods are also critical components of an integrated pest management strategy. Useful websites Penn State Tree Fruit Production Guide (https://extension.psu.edu/forage‐and‐food‐crops/fruit), Washington State Comprehensive Tree Fruit (http://treefruit.wsu.edu/crop‐protection/disease‐management/blue‐mold/), The Apple Rot Doctor (https://waynejurick.wixsite.com/applerotdr), penicillium expansum genome sequences and resources (https://www.ncbi.nlm.nih.gov/genome/browse/#!/eukaryotes/11336/). This article is a synthesis and compilation of the latest information on the mycotoxingenic blue mould fungus from multiple perspectives that entail omics, biology, and tools for decay control.